Oil and Disorder: Youth Crime in North Dakota Boom Communities - Ruddell, Rick (Criminal justice review, 2024)
Juveniles contribute to crime in natural resource-based boom communities, but there has been very little research examining the extent of their involvement. To respond to this gap in the literature, two indicators of youth arrests and court referrals in North Dakota—the state hardest hit by the 2000s oil boom—were examined. Although arrest rates for North Dakota youth were more than two times higher than the national average in 2019, almost three-quarters of them were for minor offenses. In addition, arrest and court referral rates in oil-producing counties were lower than those for non oil-producing counties. When controlling for demographic and economic factors, and county-specific fixed effects in panel analyses from 2011 to 2019, oil production is negatively associated with youth arrest rates, but positively associated with juvenile court referrals. However, oil-producing counties had very strong county-specific fixed effects which on average raised youth arrest and court referral rates. Arrest rates were also positively associated with unemployment rates while median household income was negatively associated with Group B offenses and juvenile court referrals. Implications for future research into the boom-crime relationship are discussed in light of these findings.